Evaluasi Perlakuan Pemasakan bertekanan dan Kukusan pada Karajteristik Organoleptik, Perubahan Nilai Gizi, dan Logam Berat pada Ikan Tindarung Perairan Sulawesi Utara : Evaluation of Pressure Cooking and Steaming on the Sensory Characteristics, Changes in Nutritional Value, and Heavy Metal Content of Tindarung Fish in North Sulawesi Waters - Pratiwi, Aprilia Eka; Rumengan, Inneke Fenny Melke; Sumilat, Deiske Adeline; Lintang, Rosita Anggreiny; Rengkung, Leonardus Ricky; Salindeho, Netty (Sam Ratulangi University, 2026)
North Sulawesi is one of Indonesia’s major fisheries regions, where large pelagic tuna-like species are widely consumed and commonly marketed in minimally processed forms. However, fish quality can deteriorate rapidly when post-harvest handling and thermal processing are not properly controlled. This study evaluated the effects of steam cooking and pressure-based cooking (presto) on the sensory quality, proximate composition, selected minerals, and heavy-metal levels of tindarung fish muscle collected from the Bitung Fishing Port, North Sulawesi. Fresh fish were subjected to steam cooking (15–20 min at approximately 60–100 °C) or pressure-based cooking (15 min at approximately 115 °C) and compared with fresh, untreated samples. Sensory attributes (appearance, odor, taste, and texture) were assessed in accordance with Indonesian National Standards, while proximate composition, mineral content (Ca and P), and heavy metals (Cd and Hg) were determined using standardized laboratory methods. All treatments exhibited acceptable sensory quality, with scores exceeding 6. Steam-cooked fish showed lower moisture content (63.31%) and higher protein content (27.32%) than pressure-based cooked fish (65.41% moisture; 18.65% protein). In contrast, fat content was slightly higher in pressure-based cooked fish (8.48%) than in steam-cooked fish (7.66%). Cadmium concentrations were low (0.005–0.008 mg/kg), and calcium levels in muscle were below the detection limit (<1.19 mg/kg). Total mercury concentrations ranged from 0.55 to 0.76 mg/kg, indicating that product-safety assessment should consider regulatory limits applicable to large predatory fish species. Overall, steam cooking better preserved the nutritional profile of tindarung fish and is recommended as a practical processing method, accompanied by routine mercury monitoring to ensure consumer safety. Kata kunci: tindarung fish, organoleptics, steam and pressure-based cooking, proximate composition, mineral and heavy metal level Sulawesi Utara adalah salah satu wilayah penting perikanan tangkap di Indonesia, dengan bahan pelagis besar bertipe tuna (tuna‑like species) yang banyak dikonsumsi, termasuk ikan tindarung. Mutu ikan mudah menurun apabila penanganan pascapanen dan proses perlakuan termal tidak dilakukan secara tepat. Studi ini mengevaluasi pengaruh pendekatan proses pengukusan dan pemasakan bertekanan (pemasakan bertekanan) pada mutu sensori, komposisi proksimat, mineral terpilih, dan juga kadar logam berat pada daging ikan tindarung yang diperoleh dari Pelabuhan Perikanan Bitung, Sulawesi Utara. Ikan segar diproses dengan proses pengukusan (15–20 menit; 60–100 °C) atau pemasakan bertekanan (15 menit; 115 °C), lalu dibandingkan dengan kontrol segar. Uji organoleptik (kenampakan, bau, rasa, tekstur) mengacu pada SNI, sedangkan analisis proksimat, mineral (Ca dan P), dan logam berat (Cd dan Hg) dilakukan menggunakan pendekatan uji laboratorium terstandar. Seluruh perlakuan memperlihatkan mutu organoleptik yang baik (skor >6). Ikan kukus memiliki kadar air 63,31%, abu 1,35%, lemak 7,66%, protein 27,32%, karbohidrat 0,37%, dan serat kasar 0,12%, sedangkan ikan pemasakan bertekanan memiliki kadar air 65,41%, abu 0,91%, lemak 8,48%, protein 18,65%, karbohidrat 6,55%, dan serat kasar 0,11%. Kadar Cd rendah (0,005–0,008 mg/kg), kalsium pada jaringan otot berada di bawah batas deteksi (<1,19 mg/kg), dan fosfor meningkat secara relatif sesudah pemasakan. Kadar Hg total berada pada rentang 0,55–0,76 mg/kg, dengan demikian interpretasi keamanan produk perlu mempertimbangkan kategori regulasi guna ikan predator besar dan juga kebutuhan pemantauan berkala. Pada umumnya, proses pengukusan memberikan profil gizi yang lebih menguntungkan dibandingkan pemasakan bertekanan dan direkomendasikan sebagai pendekatan perlakuan yang lebih optimal dengan tetap memperhatikan aspek keamanan, khususnya merkuri. Kata kunci: ikan tindarung, logam berat, kukus, organoleptik, pemasakan bertekanan, komposisi proksimat, kadar mineral